Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13568-018-0621-4
|View full text |Cite
|
Sign up to set email alerts
|

Hormones removal from municipal wastewater using ultrasound

Abstract: Estrogens are one of the micro-pollutants in the wastewater which have detrimental effects on water living organisms. The aim of this study was to evaluate the efficiency of ultrasound to reduce the estrogen (E1) and 17 beta-estradiol (E2) from municipal wastewater. Hence, a cylindrical batch reactor was designed. The effects of powers, frequency, exposure time and pH on reduction efficiency were investigated. The residual concentration of E1 and E2 hormones was measured in reactor effluent by electrochemilumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 53 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Municipal wastewaters from domestic and industrial sources can contain a range of different pharmaceuticals and personal care products. Such municipal effluents can be contaminated by the presence of acetaminophen [28]; diclofenac and carbamazepine [29]; ibuprofen, naproxen and triclosan [30]; and hormones [31]. Moreover, wastewater streams were reported to contain not only antibiotics from different classes (β-lactams, sulfonamides, quinolones, tetracyclines, macrolides, etc.…”
Section: Sources Of the Release Of Waste Streams Containing Pharmamentioning
confidence: 99%
“…Municipal wastewaters from domestic and industrial sources can contain a range of different pharmaceuticals and personal care products. Such municipal effluents can be contaminated by the presence of acetaminophen [28]; diclofenac and carbamazepine [29]; ibuprofen, naproxen and triclosan [30]; and hormones [31]. Moreover, wastewater streams were reported to contain not only antibiotics from different classes (β-lactams, sulfonamides, quinolones, tetracyclines, macrolides, etc.…”
Section: Sources Of the Release Of Waste Streams Containing Pharmamentioning
confidence: 99%
“…The green microalgae Selenastrum capricornutum was shown to be effective at removing hormones such as 17β-estradiol and 17α-ethinylestradiol from wastewater. Hormones in wastewater have become a major concern as they are endocrinedisrupting compounds, which can have serious negative effects on human and animal health (Roudbari & Rezakazemi, 2018 (Christenson & Sims, 2011;Hwang et al, 2016;Park et al, 2011;Posadas et al, 2017). Environmental parameters such as light intensity, light period, and temperature play a key role in influencing the performance and cost effectiveness of algal treatment systems.…”
Section: Commonly Used Microalgal Strainsmentioning
confidence: 99%
“…The green microalgae Selenastrum capricornutum was shown to be effective at removing hormones such as 17β‐estradiol and 17α‐ethinylestradiol from wastewater. Hormones in wastewater have become a major concern as they are endocrine‐disrupting compounds, which can have serious negative effects on human and animal health (Roudbari & Rezakazemi, 2018). The algae could remove 17β‐estradiol and 17α‐ethinylestradiol with a removal efficiency of 88–100% and 60–95%, respectively (Hom‐Diaz et al, 2015).…”
Section: Wastewater Reclamation By Microalgaementioning
confidence: 99%
“…Sludge disintegration process can be defined as pretreatments classified in mechanical, chemical and biological that are applied in order to improve advanced anaerobic sludge stabilization and in order to remove the unwanted pollutants. Most of the studies have shown that ultrasonic disintegration, electrokinetic disintegration and a combination of ultrasonic + electrokinetic + microbubble generation disintegration processes can be efficient in hormones [7][8][9] and pharmaceutical compounds [10][11][12] and even in polycyclic aromatic hydrocarbons removal. The aim of this study was to evaluate the efficiency of some degradation technologies for pharmaceutical (analgesic/anti-inflammatory, antipyretic) compounds (diclofenac, ibuprofen, ketoprofen, piroxicam), estrogenic hormones (estriol, equilline, estrone, 17 β estradiol, 17 α etinilestradiol, 17 α estradiol) and the PAHs (naphthalene, anthracene, phenanthrene, fluoranthene, pyrene, benz(a)anthracene, chrysene, benzo(b)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, indeno(1,2,3-cd)pyrene, benzo(ghi)perylene) in WWTP sludge samples.…”
Section: Introductionmentioning
confidence: 99%